Causes and Consequences of Tax Morale: An Empirical Investigation - Benno Torgler; Markus Schaffner (Center for Research in Economics, Management and the Arts (CREMA), 2007)
Many taxpayers truthfully declare their income to the tax administration. Why? In this paper we have found a significant correlation between tax morale and tax evasion, controlling a variety of factors. Furthermore we have analysed tax morale as dependent variable and studied the determinants that shape it. The results indicate that factors such as the tax administration, tax system, tax awareness, compliance perceptions, trust in officials and others, and the willingness to obey have a relatively strong impact on tax morale.
Keywords: H26; 330; tax morale; tax compliance; tax evasion; tax system; tax administration; social capital